Model Predictive Torque Control of Permanent Magnet Synchronous Machines. Issue 1 (July 2017) - Englert, Tobias; Grüner, Stefan; Graichen, Knut
Abstract: This contribution presents a nonlinear model predictive torque control (MPTC) scheme for permanent magnet synchronous machines (PMSMs) to provide a desired torque in an energy efficient way over a wide operational range. The MPTC relies on the nonlinear dq-model and uses a numerically efficient gradient method in combination with the augmented Lagrangian method to account for voltage and currents constraints. Simulation results show the performance and robustness of the control scheme as well as the computational efficiency and real-time feasibility.